Crystallographic and topographic analysis of ultra-translucent zirconia after various surface treatments = Análisis cristalográfico y topográfico de la zirconia ultra-translúcida después de diversos tratamientos de superficie - Vargas Koudriavtsev, Tatiana 1980-; Santamaría Villalobos, Jorge 1990- (2024)
The aim of the present study was to analyze the effects of 4 different surface treatments, on the crystallographic characteristics of Ultra-Translucent Zirconia. Fully sintered zirconia specimens of highly translucent yttria partially stabilized zirconia (Y-PSZ) (KATANA UTML) were divided into four experimental groups and a control group (n=10). Each group received one of the following surface treatments: sandblasting with 50μm alumina particles (Al2O3), sandblasting with 110μm alumina particles, and grinding with a rotary high-speed turbine with and without water irrigation. For each sample, x-ray diffraction was carried out to analyze peak intensity, calculate the crystallite size, and detect the presence of compressive and tensile stress. Surface roughness was measured on all specimens using a standard scanning profilometer. Additionally, scanning electron microscopy (SEM) was performed to qualitatively analyze the surfaces of the specimens. Statistical analysis included repeated measures analysis of variance and post hoc Tukey test (p≤0.05). The control group exhibited the highest crystallite size (323nm). All surface treatments led to a reduction in the crystallite size, with the most significant reduction observed in the groups subjected to sandblasting with 110μm alumina particles and high-speed grinding with irrigation. Sandblasting with 50μm alumina particles resulted in less transformation of the crystallite size. A general tendency of the diffraction peaks to shift to a lower angle can be observed in the experimental groups, indicating the presence of compressive stress on the samples. Profilometry revealed higher roughness in the ground samples (6,14μm and 6,57μm) compared to the sandblasted groups (2,93μm and 2,02μm). The crystal domain size showed a tendency to decrease after the surface treatments. Sandblasted samples, as well as ground samples without irrigation, exhibited compressive stress. Sandblasted samples had lower...
El objetivo del presente estudio fue analizar los efectos de 4 tratamientos de superficie en las características cristalográficas de la zirconia ultratranslúcida. Especímenes de zirconia totalmente sinterizados, altamente translúcidos de zirconia parcialmente estabilizada con itrio (Y-PSZ) (KATANA UTML) se dividieron en cuatro grupos experimentales y un grupo de control (n=10). Cada grupo recibió uno de los siguientes tratamientos de superficie: arenado con partículas de alúmina de 50μm (Al2O3), arenado con partículas de alúmina de 110μm y desgaste con una turbina rotativa de alta velocidad con y sin irrigación. Para cada muestra, se llevó a cabo una difracción de rayos X para analizar la intensidad del pico, calcular el tamaño del cristalito y detectar la presencia de tensiones compresivas y tensiles. La rugosidad superficial se midió en todos los especímenes utilizando un perfilómetro estándar. Además, se realizó microscopía electrónica de barrido (SEM) para analizar cualitativamente las superficies de los especímenes. El análisis estadístico incluyó un análisis de varianza de medidas repetidas y una prueba de Tukey post hoc (p≤0,05). El grupo de control mostró el tamaño de cristalito más alto (323nm). Todos los tratamientos de superficie llevaron a una reducción en el tamaño del cristalito, con la reducción más significativa observada en los grupos sometidos a arenado con partículas de alúmina de 110μm y desgaste de alta velocidad con irrigación. El arenado con partículas de alúmina de 50μm resultó en una menor transformación del tamaño del cristalito. Se puede observar una tendencia general de los picos de difracción a desplazarse a un ángulo más bajo en los grupos experimentales, lo que indica la presencia de estrés compresivo en las muestras. La perfilometría reveló una mayor rugosidad en las muestras con desgaste con instrumento rotatorio (en comparación con los grupos arenados. El tamaño...
En revista Odóvtos, vol. 26, no.2 (mayo-agosto 2024)
Descripción basada en el contenido visto el 04 de febrero, 2025
También disponible en formato HTML y EPUB